2002
DOI: 10.1007/s00109-002-0378-7
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin: a link between excess adiposity and associated comorbidities?

Abstract: Adiponectin is a novel polypeptide that is highly specific to adipose tissue. In contrast to other adipocytokines, adiponectin levels are decreased in obesity and associated comorbidities, such as type 2 diabetes. Decreased expression of adiponectin is correlated with insulin resistance. It has been suggested that several agents, such as tumor necrosis factor alpha, could mediate their effects on insulin metabolism through modulating adiponectin secretion from adipocytes. The mechanisms for the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
223
0
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(243 citation statements)
references
References 64 publications
7
223
0
7
Order By: Relevance
“…While body mass index did not change in either treatment group in the Ex‐DHF‐P trial,7 fat mass and detailed body composition assessments were unfortunately not available in our patients. Levels of the hormone are previously shown to be inversely correlated with body fat percentage in adults 26. Adiponectin is known to suppress TNF‐ α production and to possess direct anti‐inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…While body mass index did not change in either treatment group in the Ex‐DHF‐P trial,7 fat mass and detailed body composition assessments were unfortunately not available in our patients. Levels of the hormone are previously shown to be inversely correlated with body fat percentage in adults 26. Adiponectin is known to suppress TNF‐ α production and to possess direct anti‐inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on obese subjects showed that adiponectin levels are inversely correlated with body fat percentage in adults (Ukkola and Santaniemi 2002). Lower adiponectin concentrations in obese animals were associated with chronic inflammation, increased TNF-α, and altered glucose and insulin homeostasis (Hernandez-Bautista et al 2014).…”
Section: Adiponectinmentioning
confidence: 99%
“…Lean individuals with small adipocytes are metabolically homeostatic, but enlarged adipocytes in overweight or obese subjects promote inflammation due to macrophage recruitment. In parallel with fat mass enlargement, as the metabolic role of adipocytes changes, the secretion of various hormones, such as adiponectin, is affected (Ukkola and Santaniemi 2002;Frederich et al 1995). Since adiponectin naturally decreases with age and obesity accelerates the decline in adiponectin levels, one may speculate that obesity alters the ageing process through adiponectin regulation.…”
Section: Adiponectinmentioning
confidence: 99%
“…Adiponectin is a hormone that is secreted by adipocytes to regulate glucose and lipid metabolism [8]. The finding that adiponectin infusion reverses insulin resistance in rodent models suggests that adiponectin plays a role in this condition [9].…”
Section: Introductionmentioning
confidence: 99%